Kajian Peranan Biopori Dan Intensitas Pemupukan Terhadap Kuantitas Dan Kualitas Produksi Pepaya Calina - Muhammad Juhan; Nanik Furoidah (Universitas Muhammadiyah Jember, 2022)
Calina papaya is very popular with the public because of its rough, thick flesh texture, very sweet taste, oval-shaped fruit with medium size. The demand for calina papaya which tends to increase must be accompanied by high and continuous productivity through fertilization, for that it is necessary to do research on the intensity of fertilization and its efficiency with the application of biopori. The purpose of this study was to examine the role of biopore and fertilization intensity on the quantity and quality of calina papaya production. The study was carried out in the generative phase in the rice fields of Kemuning Sari Kidul village (50 m asl), Jenggawah District, Jember Regency using a randomized block design (RBD) with a 3 x 3 factorial pattern and repeated three times. The factors studied were the number of biopori (B) per tree consisting of B1 = 4 biopori per tree; B2= 3 biopori per tree; B3 = 2 biopori per tree and fertilization intensity (I) consists of I1 = fertilization 1 time per month; I2= fertilization 2 times per month; I3 = fertilization 3 times per month. The results showed that the intensity of fertilization 3 times per month significantly resulted in the highest fruit weight and sugar content. The fruit weights in the 2nd and 3rd measurements were 1.83 kg and 1.72 kg, respectively, the subsequent measurements were not significantly different, ranging from 1.1 to 1.3 kg, the intensity of fertilization 3 times per month also resulted in higher sugar content, namely 14 -15% brix. The combination of 4 biopore holes and fertilization intensity 3 times per month (B1I3) resulted in higher fruit weight at the 6th measurement, namely 1.33 kg. The intensity of fertilization and the use of biopori on the parameters of productive internodes and abnormal fruit did not show a significant difference.